Marketing 6.0 the future is immersive - Kotler, Philip 1931-; Kartajaya, Hermawan 1947-; Setiawan, Iwan (Wiley, 2024)
Young Generation Z and Generation Alpha Coming of Age -- CHAPTER 3 The Inevitability of Immersive Marketing: Five Micro-Trends Leading to Metamarketing -- Short-Form Video Content -- Community-Based Social Media -- Interactive E-Commerce -- Language-Based AI -- Immersive Wearable Devices -- Summary: Five Micro-Trends Leading to Metamarketing -- CHAPTER 4 The Future of Customer Experience: Fusing Physical and Digital for Complete Immersion -- The Future Is Immersive -- The Future Is Also Hybrid -- No One-Size-Fits-All Strategy -- Summary: Fusing Physical and Digital for Complete Immersion